2003
DOI: 10.1038/sj.cdd.4401288
|View full text |Cite
|
Sign up to set email alerts
|

Serine proteases mediate apoptosis-like cell death and phagocytosis under caspase-inhibiting conditions

Abstract: Effective execution of apoptosis requires the activation of caspases. However, in many cases, broad-range caspase inhibitors such as Z-VAD.fmk do not inhibit cell death because death signaling continues via basal caspase activities or caspase-independent processes. Although death mediators acting under caspase-inhibiting conditions have been identified, it remains unknown whether they trigger a physiologically relevant cell death that shows typical signs of apoptosis, including phosphatidylserine (PS) exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
121
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 64 publications
4
121
0
Order By: Relevance
“…Phase-contrast microscopy revealed that inhibition of the proteasome with either lactacystin, MG262, or epoxomycin, protected cells from ER stress (BFA/CHX, for 24 h) to the same extent as Pefabloc ( Figure 1a). As was previously shown, we saw that caspase inhibition with either Z-VAD.fmk or Q-Val-Asp-(non-O-methylated)-OPh (Q-VD-Oph) ( Figure 1a and data not shown) did not prevent cells from undergoing ER stressinduced cell death, 11 and CHX treatment alone did not induce cell death (Figure 1a). …”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…Phase-contrast microscopy revealed that inhibition of the proteasome with either lactacystin, MG262, or epoxomycin, protected cells from ER stress (BFA/CHX, for 24 h) to the same extent as Pefabloc ( Figure 1a). As was previously shown, we saw that caspase inhibition with either Z-VAD.fmk or Q-Val-Asp-(non-O-methylated)-OPh (Q-VD-Oph) ( Figure 1a and data not shown) did not prevent cells from undergoing ER stressinduced cell death, 11 and CHX treatment alone did not induce cell death (Figure 1a). …”
Section: Resultssupporting
confidence: 76%
“…* Po0.001 treated versus untreated Z-VAD.fmk and Q-VD-OPh did not impose a complete block in ER stress-induced cell death (Figures 1 and 2, Ref. 11 and data not shown). This suggests that some fraction of the caspase-3 processing associated with BFA/CHX treatment might only be an epiphenomenon, and is not a key player in this pathway.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations